A single-center retrospective analysis of postoperative self-care in PANDO patients undergoing endoscopic nasal dacryocystorhinostomy (En-DCR) under the day-ward model - LIU Yunming; ZHENG Xinyu; XIAO Lixia; LI Shuiling (Yanke Xuebao)
[Objective:] To investigate postoperative self-care practices and evaluate the early outcomes of patients with Primary Acquired Nasolacrimal Duct Obstruction (PANDO) undergoing Endoscopic Dacryocystorhinostomy (En-DCR) in a day ward setting. [Methods:] 90 PANDO patients who underwent En-DCR surgery at the Oculoplastic and Lacrimal Surgery day ward at Zhongshan Ophthalmic Center, Sun Yat-sen University, between November 2021 and August 2022, were enrolled in this study. All patients received standardized postoperative self-care instructions. At the one-month follow-up, a questionnaire survey was used to record patients' self-care adherence to self-care practices, postoperative discomfort symptoms, and assess surgical outcomes. Furthermore, the correlation between self-care factors and surgical outcomes/discomfort symptoms was explored. [Results:] A total of 90 eyes from 90 PANDO patients undergoing En-DCR were included. The overall surgical success rate at one month was 92.22% , comprising a cure rate of 65.56% and an improvement rate of 26.67%. Analysis of self-care practices related to surgical outcomes showed significantly better results in patients who adhered to nasal irrigation at least once daily (P=0.002), used prescribed nasal spray at least once daily (P=0.008), and avoided upper respiratory tract infections (P=0.047). Regarding postoperative discomfort, patients who performed nasal irrigation at least once daily (P=0.006) and had the lacrimal stent (tube) in situ (P=0.003) experienced significantly fewer symptoms. Furthermore, correlation analysis in stented patients indicated a positive correlation between stent discomfort and psychological burden (r=0.421, P<0.001). [Conclusion:] In the day ward model, detailed self-care guidance provided by healthcare professionals for En-DCR patients contributes to postoperative recovery and ensures favorable surgical outcomes. Key instructions include performing nasal irrigation at least once daily, using anti-inflammatory nasal spray regularly, and preventing upper respiratory infections during the first postoperative month. Additionally, particular attention should be paid to localized discomfort in patients with lacrimal stents. Optimizing medication regimens for discomfort, utilizing internet-based nursing clinics or telephone follow-ups for guidance and psychological support are crucial to promote postoperative rehabilitation.